Pengaruh Tingginya Temperatur Minyak Lumas terhadap Kinerja Mesin Diesel Generator di Kapal - Moh Ghufron Muhtadi; Eko Prayitno; Kuntoro Bayu Ajie; Antonius Edy Kristiyono; Novitasari Novitasari (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study was conducted based on the crucial role of diesel generator engines as the primary source of electrical power on board ships, making their operational reliability essential. One of the factors influencing generator engine performance is lubricating oil temperature. Excessive lubricating oil temperature may reduce lubrication effectiveness, increase friction between moving components, and lower engine efficiency. Therefore, this research aimed to identify the causes of high lubricating oil temperature in diesel generator engines and determine appropriate corrective actions. The study employed a descriptive quantitative approach. Data were collected through direct observation, interviews, and documentation during sea practice aboard MV. CL FLANDERS from 4 July 2024 to 5 July 2025. The data were analyzed using simple linear regression to examine the relationship between generator load and lubricating oil temperature. The findings revealed that generator load had a significant effect on the increase in lubricating oil temperature. Under normal operating conditions, the lubricating oil temperature ranged from 60°C to 72°C, while under abnormal conditions it increased to between 68°C and 81°C. The abnormal rise in temperature was mainly caused by cooling system problems, particularly a dirty LO cooler, scale deposits on the sea water pump impeller, and blockage in the cooling capillary pipes. The regression equation under normal conditions was Y = 45 + 0.30X, whereas under abnormal conditions it was Y = 53.5 + 0.30X. Elevated lubricating oil temperature resulted in lower oil viscosity, higher fuel consumption, and reduced diesel generator engine performance. Therefore, regular maintenance of the LO cooler, sea water pump, and continuous temperature monitoring are necessary to maintain optimum engine performance.